2002
DOI: 10.1093/aob/mcf256
|View full text |Cite
|
Sign up to set email alerts
|

Allozyme Diversity in Natural Populations of Viola palmensis Webb & Berth. (Violaceae) from La Palma (Canary Islands): Implications for Conservation Genetics

Abstract: Genetic diversity was measured by allozyme electrophoresis in eight natural populations of the threatened Canarian endemic Viola palmensis Webb & Berth. (Violaceae). Nineteen alleles corresponding to 11 gene loci were detected. High levels of genetic diversity were found, ranging from 36.3 to 45.4 % for the percentage of polymorphic loci (P), from 1.45 to 1.60 for the average number of alleles per locus (A) and from 0.128 to 0.200 for the expected heterozygosity (H(e)). Between 85.5 and 96.6 % of genetic varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 10 publications
4
21
0
Order By: Relevance
“…Thus, although Eguiarte et al (1992) found a similar value to P. canariensis' in the rain forest palm Astrocaryum mexicanum (He ¼ 0.153), lower values were described in Carpentaria acuminata, (He ¼ 0.143), Ptychosperma bleeseri (He ¼ 0.006) and Pinanga tenella (He ¼ 0.133) (Shapcott, 1998a(Shapcott, , b, 1999 and in Washingtonia filifera (He ¼ 0.008) (McClenaghand and Beauchamp, 1986). This result agrees with other studies that show higher genetic diversity levels in Canarian endemic plants than in those distributed in other oceanic islands (Francisco-Ortega et al, 2000;Batista et al, 2001;Batista and Sosa, 2002;Bouza et al, 2002). On the whole, the three groups of populations exhibited higher genetic variability values than species with similar life history traits (monocotyledons, endemics and species with sexual reproduction).…”
Section: Discussionsupporting
confidence: 86%
“…Thus, although Eguiarte et al (1992) found a similar value to P. canariensis' in the rain forest palm Astrocaryum mexicanum (He ¼ 0.153), lower values were described in Carpentaria acuminata, (He ¼ 0.143), Ptychosperma bleeseri (He ¼ 0.006) and Pinanga tenella (He ¼ 0.133) (Shapcott, 1998a(Shapcott, , b, 1999 and in Washingtonia filifera (He ¼ 0.008) (McClenaghand and Beauchamp, 1986). This result agrees with other studies that show higher genetic diversity levels in Canarian endemic plants than in those distributed in other oceanic islands (Francisco-Ortega et al, 2000;Batista et al, 2001;Batista and Sosa, 2002;Bouza et al, 2002). On the whole, the three groups of populations exhibited higher genetic variability values than species with similar life history traits (monocotyledons, endemics and species with sexual reproduction).…”
Section: Discussionsupporting
confidence: 86%
“…This is in very clear contrast to the previously reported inbreeding coefficients on other Viola species. Batista and Sosa (2002) reported F IS = 0.375 for V. palmensis based on isozyme analysis. Culley and Wolfe (2001) reported F IS = -0.09 for V. pubescens based on isozyme analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The amount of genetic variation and differentiation among populations can be influential in habitat management and species preservation, especially in the case of rare and endangered species Hamrick 1993, 2001;Batista and Sosa 2002). An AFLP study on the Federally endangered Kanab ambersnail (Oxyloma haydeni kanabensis) provided resource managers with the genetic data to establish that the two surviving populations are genetically distinct and should be protected (Miller et al 2000).…”
Section: Conservation and Managementmentioning
confidence: 99%